Efek Pemasaran Melalui Media Sosial Terhadap Minat Konsumen Dalam Bertransaksi Ulang - M Noer Andika Pratama; Naufal Nur Abid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research explores the impact of marketing strategies that use social media on consumers' interest in making repeat purchases. Social media has become a significant platform in influencing consumer behavior. By integrating effective marketing strategies on social media, this research aims to understand how consumers' interactions with advertising and promotional content on social media influence their desire to make repeat purchases. Quantitative and qualitative research methods were used to analyze data from surveys and interviews with consumers who actively use social media. The results show a significant relationship between exposure to social media advertising and consumers' interest in repeat transactions, with factors such as brand trust and consumer engagement playing an important role in this process.